Eulerian and Lagrangian analyses of bioaerosol transport in three deep convective storm morphologies - Davis, Charles M., author; van den Heever, Susan C., advisor; Kreidenweis, Sonia M., committee member; Jathar, Shantanu, committee member (Colorado State University. Libraries, 2025)
In this thesis, we investigate the entrainment and transport of aerosol particles in a representative isolated deep convective storm, supercell, and squall line using idealized high-resolution mesoscale model simulations. We focus our investigation on the extent to which air from rainy surface regions, which have been noted in the literature to be sites of aerosolization of biological particles, is able to enter and subsequently be transported within these storm morphologies. We also investigate the residence time in supersaturated environments experienced by these parcels as they are entrained. The first part of this study quantifies the magnitude and timing of entrainment of air from the surface, and from rainy surface regions specifically, in all three storm morphologies. We use inert tracer quantities to constrain the timing with which rainy (referred to as rain-sourced tracers) and other surface air (referred to as fixed-source tracers) is entrained into the storms, and the fraction of each storm's updraft that is composed of air from these regions. At its peak, the isolated convective storm entrains the greatest proportion of surface-based air seen in any of the storms. However, it also attains the smallest concentrations of rain-sourced tracer and the smallest proportion of rain-sourced tracer in its updraft, indicating that significantly less of its entrained surface air originates in regions of potential rain-induced aerosolization of bioaerosols. The squall line and supercell attain greater values of both these quantities and sustain them for longer periods, indicating that more air in their updrafts originates in rainy regions. For light rain (>= 1 mm/hr), the squall line and supercell entrain comparable concentrations of air from rainy regions, but for heavy rain (>= 40 mm/hr) the squall line entrains significantly more. The second part of this work investigates the specific pathways by which surface air is entrained into these storms as well as the environments experienced by entrained surface-based air parcels. We do this by calculating parcel trajectories using the output of the aforementioned mesoscale simulations, initializing air parcels at various times within each storm's life cycle, and separately evaluating the trajectories of parcels originating in rainy and non-rainy regions. The isolated convective storm simply moves over and entrains the parcels not initialized in rainy regions into its updraft directly by its strong surface convergence. The squall line and supercell entrain non-rainy parcels by gust-front lofting, in which the circulation at the leading edge of the cold pool lofts the parcels to a level at which they can be entrained by the updraft behind the gust front. The isolated convective storm entrains parcels originating in rainy regions via the horizontal vortical circulation in the head of the cold pool, which lofts them and redirects them towards the updraft. The squall line also entrains rainy parcels by this same circulation in its cold pool. The supercell, on the other hand, entrains rainy parcels from a relatively narrow region within and just outside of the leading edge of the forward-flank downdraft's cold pool via a combination of gust front lofting and the known phenomenon of the "recycling" of some negatively buoyant air from the forward-flank downdraft's cold pool into its updraft. We find that the time these entrained parcels spend in supersaturated environments is a strong function of storm morphology. Parcels entrained into the squall line spend nearly twice as long on average in supersaturated regions as entrained parcels in the other two storm types. This arises because the squall line parcels take longer to reach mid-levels after first being lofted by the circulation in the head of the cold pool. This longer transit time is due to the upshear tilt of the updraft, as well as from more complex 3D variations in the structure of the gust front and updraft.
Keywords: bioaerosols; deep convection; Lagrangian; convective storms; aerosol transport; Eulerian